Challenges to regional intergration in the SADC region : a legal perspective - Mwanawina, Ilyayambwa (North-West University, 2011)
The Southern African Development Community (SADC), formerly known as the Southern African Development Coordination Conference (SADCC), is an organization of Southern African states initially formed to reduce economic dependence on South Africa (then an Apartheid state) and to harmonize and coordinate development in the region. The vision and mission of SADC reach well beyond the harmonization of development within the region. It extends to fields that include political stability, peace building, the maintenance of security and justice as well as economic cooperation. The attainment of these goals requires well co-ordinated regional mechanisms; as such over the past decade member states have paid particular attention to the possibility of attaining these goals through regional integration. The transformation from SADCC to SADC indicated that the body would no longer be a loose association (conference) of states but rather a regional body that would have a legally binding effect on its member states. The question is, when the member states assembled in Windhoek, August 1992, did they create an institutional framework, and policies that would have enough legal force to ensure that the institutional agenda of integration is not defeated by member states? The argument of this dissertation is that the Treaty and the policies established afterwards contain principle imperfections that are self defeating for the pursuance of regional integration. The work will begin by discussing regional integration in general, highlighting the historical origins of SADC as well as the role of the African Union. The work will then discuss the dimensions and functioning of SADC, laying the foundation for a proper critique on how the institutional framework contains inherent weaknesses that eventually hinder the progression of SADC. The dissertation ultimately will discuss and benchmark the European Union against SADC, in an attempt to extract important lessons for the progression of SADC.
Accepted: 2016-01-10T22:52:56Z https://repository.nwu.ac.za/handle/10394/15788
Keywords: Africa; Interregionalism; Southern

International convention for the control and management of ships' ballast water and sediments, 2004 - Robe Hughes, Charlotte (Aix-Marseille Université, 2011)
Will harmonization of legislation relating to the management of ships’ ballast water be achieved, once IMOs’ 2004 Convention enters into force?